2020
DOI: 10.1088/2053-1591/ab6932
|View full text |Cite
|
Sign up to set email alerts
|

The effect of precursor concentration and post-deposition annealing on the optical and micro-structural properties of SILAR deposited SnO2 films

Abstract: Uniform and well-adherent SnO 2 thin films, with thickness ranging from 60 nm to 6 μm, were deposited on borosilicate glass substrate by Successive Ionic Layer Adsorption and Reaction (SILAR) technique. A micro-controlled SILAR unit was employed to precisely monitor the deposition conditions. The effect of precursor concentration and post-deposition annealing on the micro-structural and optical properties of SnO 2 thin films were studied in detail. The films were found to possess tetragonal rutile structure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The excess Sn 4+ ions attached to the VAG surface were removed by rinsing with deionized water. The VAG electrode immersed in H 2 O 2 aqueous solution underwent a reaction as described in eq , resulting in amorphous SnO 2 nanoparticles on the surface . Similar to the previous step, the excess ions on the VAG surface were removed by rinsing with deionized water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The excess Sn 4+ ions attached to the VAG surface were removed by rinsing with deionized water. The VAG electrode immersed in H 2 O 2 aqueous solution underwent a reaction as described in eq , resulting in amorphous SnO 2 nanoparticles on the surface . Similar to the previous step, the excess ions on the VAG surface were removed by rinsing with deionized water.…”
Section: Resultsmentioning
confidence: 99%
“…Figure illustrates the preparation of SnO 2 @VAG using the S-SCBD process. The VAG electrode was sequentially immersed in cationic and anionic precursor solutions for 30 s. When VAG was immersed in a cationic aqueous solution, the Sn 4+ ions in the cationic solution adhered to the VAG surface, following eq . The excess Sn 4+ ions attached to the VAG surface were removed by rinsing with deionized water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the MnCl 2 -derived Mn 3 O 4 electrode showed a good electrochemical with maximum energy density of 17 Whkg À1 and power density of 999 Wkg À1 at 0.5 mAcm À2 current density showing retention stability of 94% after 4500 CV cycles [160]. Besides, a study of SILAR-deposited SnO 2 films showed improvement of the crystallite with solution molarity performed by using different precursor concentration of both cations and anions [161].…”
Section: Effect Of Precursorsmentioning
confidence: 88%